If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -6x = 3x + 16 Reorder the terms: 65 + -6x = 16 + 3x Solving 65 + -6x = 16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 65 + -6x + -3x = 16 + 3x + -3x Combine like terms: -6x + -3x = -9x 65 + -9x = 16 + 3x + -3x Combine like terms: 3x + -3x = 0 65 + -9x = 16 + 0 65 + -9x = 16 Add '-65' to each side of the equation. 65 + -65 + -9x = 16 + -65 Combine like terms: 65 + -65 = 0 0 + -9x = 16 + -65 -9x = 16 + -65 Combine like terms: 16 + -65 = -49 -9x = -49 Divide each side by '-9'. x = 5.444444444 Simplifying x = 5.444444444
| (12X+8)+(12X-3)+(6X+25)=180 | | 147-4x=32x+15 | | 13-10x=108-45x | | 5x^2-36x+36=0 | | 2(4x+1)+8=56 | | X=60+-4x | | 3h-7h+2=14 | | 50-5x=13x+24 | | 34-2x=7x+17 | | 5a^8-5a^7-10a^6= | | 11x-9x=106-44x | | X+(x+2)+3(x+2)=68 | | -16-9x=8x+18 | | s-9=25 | | 5x+8=-44-8x | | x+x/2+2x+10=32 | | 5m+2=6m-2 | | 11=5x-24 | | 5x-25=3x+25 | | 2y+x=21 | | 10-7x=75-42x | | 6x+7=43whatisx | | -(-y-3z-5)= | | 4-8x=3+9x | | 89-4x=14x+19 | | 2y^2-y-.5= | | 3x+5=x+6 | | 14-10x=71-31x | | (((x)+2)*3)=68 | | x+3x+10=10+10 | | 0=x^2+2x-81 | | 5x-11=3x |